Making a Difficult Language Skill Easy - Tchaparian, Vicky (Armenian Folia Anglistika, 2016)
One of the main reasons why writing is a difficult language skill according to Roger and Robinson is that “the connection between the mind and the verbal system, by which mental processes are made apparent (visible or audible) to oneself and to others, is difficult to capture” (Roger and Robinson 1990:88). However, one can overcome writing difficulties by following certain rules. This paper intends to introduce rules for better writing.